2020
DOI: 10.4102/sajbm.v51i1.2046
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mobile advertising wearout on consumer irritation, perceived intrusiveness, engagement and loyalty: A partial least squares structural equation modelling analysis

Abstract: Research showed that marketers and advertisers in the United States will spend around $43.9 billion this year on mobile advertisements (ads) (Benes, 2019). Computing has become prevalent in personalised marketing, which is why mobile devices are highly individualised and are important personal communication tools (Bacile, Ye, & Swilley, 2014). Shawky, Kubacki, Dietrich and Weaven (2019) argued that less accessible consumer segments can be reached through social media and mobile platforms ads. Existing literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 66 publications
4
17
1
Order By: Relevance
“…It is commonly believed that when consumers who are exposed to advertising become irritated, which has negative consequences on ad value (Lee et al., 2017). It could be assumed that when we use digital technologies, such as smartphones, the irritability effect disappears (Tsang et al., 2004); however, consumers are exposed to advertising by the simple fact of using smartphones, which produces an ad wear‐out effect (Alwreikat & Rjoub, 2020), leading them to perceive equal irritation and thus negatively impacting ad value (Lee et al., 2017). However, even on social media, where entertainment is a key factor, if consumers feel irritated by advertising, they will tend to avoid it by one means or another (Niu et al., 2021).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…It is commonly believed that when consumers who are exposed to advertising become irritated, which has negative consequences on ad value (Lee et al., 2017). It could be assumed that when we use digital technologies, such as smartphones, the irritability effect disappears (Tsang et al., 2004); however, consumers are exposed to advertising by the simple fact of using smartphones, which produces an ad wear‐out effect (Alwreikat & Rjoub, 2020), leading them to perceive equal irritation and thus negatively impacting ad value (Lee et al., 2017). However, even on social media, where entertainment is a key factor, if consumers feel irritated by advertising, they will tend to avoid it by one means or another (Niu et al., 2021).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Figure 9(c) is related to the impact of rework (RE) and doing things right first (DR) variables on the output variable, which is performance measuring (PE). When the DR is in its high values in the range of 4 to 6 and RE is between 2 and 4, the output will be more than average (4). On the other hand, as shown in Figure 9(d), when both input variables of RE and management information (MI) system get high values, the output, PM, is higher than the average.…”
Section: Fuzzy Logic Resultsmentioning
confidence: 95%
“…e development of new products helps organizations to maintain their competitive and monopoly position in the market. Introducing the development of new products' strategies, models, and processes plays a crucial role for all types of organizations and their long-term survival [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Advertising frequency is necessary for brand awareness, with a high number of repetitions increasing the persuasion and advertising recall (Alwitt and Mitchell 1985). Alwreikat and Rjoub (2020) found that repetitive advertising resulted not only in irritation, but also reduced levels of customer engagement.…”
Section: Advertising Strategiesmentioning
confidence: 99%